EDITORIAL - Isoldi, Liercio Andre (Revista de Engenharia Térmica, 2018)
Since 1996, the Constructal Theory, developed by Adrian Bejan, scientifically explains that the design generation in nature is governed by a physical principle called Constructal Law, which states that "for a finite-size flow system to persist in time (to survive) it must evolve in such a way that it provides easier and easier access to the currents that flow through it". This principle can be applied in engineering through the Constructal Design Method. Constructal Design is the philosophy of evolutionary design in engineering applications. Nowadays the Constructal Design Method has been widely employed in heat transfer and fluid mechanics areas, allowing understanding how the geometric configuration influences the system performance. In addition, the association of Constructal Design with some optimization method (for instance Exhaustive Search or Genetic Algorithm) will enable to determine the optimized geometry of the system, i.e., the system design that conduct to a superior performance. In the opinion of Engenharia Térmica the approach based on Constructal Theory, Constructal Law and Constructal Design can be adopted to understand and improve engineering systems involving heat transfer and/or fluid mechanics.